2015
DOI: 10.2166/wst.2015.085
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a pilot showcase of different wetland systems in an urban setting in Singapore

Abstract: The Alexandra Wetlands, part of PUB's Active, Beautiful, Clean Waters (ABC Waters) Programme, showcase a surface flow wetland, an aquatic pond and a sub-surface flow wetland on a 200 m deck built over an urban drainage canal. Water from the canal is pumped to a sedimentation basin, before flowing in parallel to the three wetlands. Water quality monitoring was carried out monthly from April 2011 to December 2012. The order of removal efficiency is sub-surface flow (81.3%) >aquatic pond (58.5%) >surface flow (50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…In the 24‐h monitoring period, approximately 56.5% of NH 4 ‐N was transformed in the wetland system (Figure b). By comparison, Quek et al reported TN removal efficiencies of 22.0–44.9% in various types of CWs for treating stormwater at Alexandra Wetlands in Singapore. A comparable finding was also revealed by Terzakis et al who observed a TN removal of 49% on average in CWs treating highway runoff in the central Mediterranean region.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the 24‐h monitoring period, approximately 56.5% of NH 4 ‐N was transformed in the wetland system (Figure b). By comparison, Quek et al reported TN removal efficiencies of 22.0–44.9% in various types of CWs for treating stormwater at Alexandra Wetlands in Singapore. A comparable finding was also revealed by Terzakis et al who observed a TN removal of 49% on average in CWs treating highway runoff in the central Mediterranean region.…”
Section: Resultsmentioning
confidence: 99%
“…Birch et al reported that the average RE of NO x , total nitrogen (TN), total Kjeldahl nitrogen, and total phosphorous (TP) was 22, 16, 9, and 12%, respectively. In comparison, Quek et al evaluated the performance of a pilot showcase of different wetland systems in an urban setting in Singapore, and reported the RE of 50.7–81.3% for total suspended solids (TSS), 22.0–44.9% for TN, and 5.4–56.7% for TP, respectively. Wetland configurations, flow rate, wastewater type, and plant species, among other operational variables, can affect the performance of wetland systems with respect to water treatment .…”
Section: Introductionmentioning
confidence: 99%
“…Identify and profile the most influential authors, institutions, and journals in the SUDS domain (Pozo et al, 24 February 2021). Utilize VosViewer to showcase authorship networks, citation indices, and institutional collaborations, providing insights into the key players shaping the field (Quek et al, 2015). Analyze the emerging themes and keywords within the SUDS literature (Ritzema, February 2014).…”
Section: Research Significancementioning
confidence: 99%
“…Although neither GI, BGI, nor ecosystem services are mentioned, the ABC Waters Program exemplifies a shift from gray infrastructure to BGI in urban water management, showcasing a BGI-building program for a high-density city. Despite the ABC Waters Program has been carried out for more than a decade and has received several international awards, its literature remains limited to the technical aspects of stormwater management (e.g., Goh et al 2017;Quek et al 2015). Lim and Lu (2016) provide a comprehensive review of the program, but only as a stormwater management program.…”
Section: Introductionmentioning
confidence: 99%